2014
DOI: 10.1111/hepr.12319
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy increases the number of circulating hematopoietic stem/progenitor cells in patients with hepatitis C virus‐associated liver cirrhosis

Abstract: Our data suggest that the spleen plays an important role in modulating HSC dynamics in patients with HCV-associated chronic liver disease. Our results also imply that splenectomy may improve liver function in patients with LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…Therefore, decline of these factors by splenectomy and high albumin levels could promote liver regeneration, as shown in the present study. Moreover, splenectomy is thought to modulate hepatic stellate cells and immunological changes . We have also reported that splenectomy provided protective effects for liver failure and promoted liver regeneration, possibly owing to the downregulation of immediate early response genes and upregulation of the heat shock protein, heme oxygenase‐1 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, decline of these factors by splenectomy and high albumin levels could promote liver regeneration, as shown in the present study. Moreover, splenectomy is thought to modulate hepatic stellate cells and immunological changes . We have also reported that splenectomy provided protective effects for liver failure and promoted liver regeneration, possibly owing to the downregulation of immediate early response genes and upregulation of the heat shock protein, heme oxygenase‐1 .…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the effects of splenectomy have been studied from many aspects. The spleen plays an important role in modulating hepatic stellate cell dynamics in patients with hepatitis C virus (HCV)‐associated chronic liver disease, and splenectomy may improve liver function in patients with LC . On the other hand, splenectomy may improve liver fibrosis and cause beneficial immunological changes in cirrhotic patients with hepatitis, and improvements in antitumor mechanisms can also be expected .…”
Section: Introductionmentioning
confidence: 99%
“…The spleen is known to contribute extensively to blood regeneration in conditions of stress, such as anaemia or injury-induced stress erythropoiesis, or in response to infections, when HSPCs from the BM actively migrate into the spleen and proliferate there (Griseri et al, 2012;Harandi et al, 2010;Lenox et al, 2005;Masuya et al, 2014;O'Malley et al, 2005). The role of tissue-resident HSPCs in these responses has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The spleen, for example, was the first organ reported to contain stem and progenitor cells that are able to rescue irradiation-induced haematopoietic failure (Jacobson et al, 1951). Today, the splenic red pulp is recognized as one of the most common sites for EMH in response to haematopoietic challenges like anaemia (Harandi et al, 2010;Lenox et al, 2005;Perry et al, 2007), increased demand of blood cells during pregnancy (Inra et al, 2015;Maymon et al, 2006;Nakada et al, 2014;Oguro et al, 2017); and various pathologies, such as myeloproliferative disorders (O'Malley et al, 2005) and chronic inflammation/infection (Griseri et al, 2012;Masuya et al, 2014). Mechanistically, upon BM injury or stress, BM HSPCs traffic to the spleen and are attracted to specific stromal cells producing SCF and CXCL12 (Inra et al, 2015;Miwa et al, 2013;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we futher confirmed the efficacy of splenectomy in the improvement of cytopenia associted with hypersplenism in WD patients with liver cirrhosis. Recently, literatures have shown that splenectomy can improve liver function in patients with liver cirrhosis caused by hepatitis C or by advanced hepatocellular carcinoma [ 31 , 32 , 33 ]. Here, we also show the long-term beneficial effect of splenectomy on liver function in WD patients with hypersplenism and liver cirrhosis, though the deterioration of liver function was observed shortly after splenectomy.…”
Section: Discussionmentioning
confidence: 99%